Predictable Dynamics in the Implied Volatility Surface Based on Weighted Least Squares: Evidence from Soybean Meal Futures Options in China. Issue 11 (1st September 2020) - Sui, Cong; Lung, Peter; Yang, Mo
ABSTRACT: This article examines the dynamics and predictability of the implied volatility surface derived from weighed trading volume. We study the Chinese soybean meal futures options market. By assigning larger weights to options with higher trading volume, we find more precise fittings on the implied volatility surface. Our estimation method outperforms traditional methods in terms of the dynamics and predictability of the implied volatility surface, both in the sample and out of the sample. We also document that soybean futures options exhibit implied volatility smirk that is different from those in the stock index options. In addition, we find that the implied volatility term structure shows an inverted U -shape during the period of high implied volatility.